Relevansi Kompilasi Hukum Islam Dengan Madzhab Hanafiyyah: Studi Hadits Persetujuan Perempuan Dalam Perkawinan - Moh. Dliya'ul Chaq (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2020)
Paragraph 1, article 6 KHI and fiqih madzhab hanafiyyah both state the mandatory approval of the prospective bride. The similarity between the two raises the proposition that the article on women's consent in the KHI is relevant to the hanafiyyah school of thought. But in reality, the logical formulation sequence of the hanafiyyah version of the agreement law is built on the basic understanding that women have rights rather than their guardians so that guardians have no rights in marriage, seemingly incompatible with the Islamic Law Compilation. This encourages the importance of the hadith study on women's consent. Through a literature review (library research) with a comparative analytical descriptive model, it is concluded; First, the hadith for women's consent is understood by hanafiyyah that women are more entitled than their guardians to the agreement, contract and other things. In other languages, guardians do not have rights over their daughters so that guardians are not a condition or harmonious in marriage. Second, there is no relevance between KHI and fiqih madzhab hanafiyyah, because in the legal construction between the two is different, where women's approval of their marriage in the hanafiyyah school is based on the basic stipulation that the guardian does not have the authority to approve or marry so that the guardian is not needed in marriage, while KHI states that women only have the authority to approve their marriage while still giving marriage authority to the guardian of marriage.